An increasing disinterest in fatherhood among childless men in the United States: A brief report. Issue 1 (30th July 2022) - Bozick, Robert
Abstract: Objective: The goal of this brief report is to document trends in expectations for and attitudes toward fatherhood among childless men across the first two decades of the 2000s. Background: Childless men account for more than a third of adult men in the United States, but it is unclear if they desire to become fathers, and if not, whether this sentiment changed over time. Method: Time trends for multiple measures of expectations for and attitudes toward fatherhood are plotted using samples of childless men from the National Survey of Family Growth, the Monitoring the Future study, and the Panel Study of Income Dynamics' Transition to Adulthood supplement. Results: Across the time series, a growing share of childless men do not want children and increasingly, a lack of children would not bother them at all. Additionally, certainty in having children among childless men has waned over time and fewer childless men are concerned with parental leave policies when evaluating their job options. Conclusion: Across the first two decades of the 2000s, there is an increasing disinterest in becoming fathers among childless men. These trends have broad implications for family researchers who study fertility rates, men's health, and family relationships.